PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PENJUALAN MELALUI INOVASI PRODUK SEBAGAI VARIABEL INTERVENING PADA USAHA KECIL DAN MENENGAH BATIK TULIS LASEM KABUPATEN REMBANG - Arga Dristianto; Rodhiyah Rodhiyah (Jurnal Ilmu Administrasi Bisnis, 2016)
The presence of SMES Batik Lasem always experience a variety of obstacles, namely human resources are low and their lack of knowledge. Knowledge became an important capital in running the business. The purpose of this research is to know the influence of intellectual capital against sales performance through product innovation as the intervening variables on Batik Lasem SMES. The research type is explanatory research with a sample of 58 respondents as business owners and the sampling technique used is a sampling of saturated. Data analysis using SPSS for Windows version 7.0. Where previously used test the validity, reliability, coefficient of correlation, simple and multiple regression analysis, the determination coefficient, test of significance (t-test and F-test) as well as medote sobel. The results of the analysis indicate the presence of influence between intellectual capital to innovation of products, obtained the results of correlation of 0.401 worth being, the contribution of intellectual capital to innovation of products amounted to 16.1%. The presence of the influence between product innovation against sales performance, the correlation of results obtained 0.333 low value, the contribution of product innovation performance against sales by 11.1%. While intellectual capital has no effect on performance of the sale. Test the 0.084 acquired for correlation value is very low with the contribution amounted to 0.07%. Intellectual capital and innovation products take effect significantly to sales performance with the F-count >F-table (3.536>3.162). Then on the path analysis and the sobel test using preacher tool, there is the influence of intervening product innovation in the relationship of intellectual capital against Batik SME sales performance.